Immunochromatographic assay based on time‐resolved fluorescent nanobeads for the rapid detection of sulfamethazine in egg, honey, and pork. (21st August 2020) - Wang, Zexiang; Hu, Song; Bao, Huanhuan; Xing, Keyu; Liu, Jintao; Xia, Jun; Lai, Weihua; Peng, Juan
Abstract: BACKGROUND: Sulfamethazine (SMZ), a veterinary drug widely used in animal husbandry, is harmful to human health when excess residues are present in food. In this study, a fast, reliable, and sensitive immunochromatographic assay (ICA) was developed on the basis of the competitive format by using time‐resolved fluorescent nanobeads (TRFN) as label for the detection of SMZ in egg, honey, and pork samples. RESULTS: Under optimized working conditions, this method had limits of detection of 0.016, 0.049, and 0.029 ng mL −1 and corresponding linear ranges of 0.05 to 1.00, 0.05 to 5.00, and 0.05 to 1.00 ng mL −1 in egg, honey, and pork samples, respectively. The recovery experiments showed that the average recoveries ranged from 90.5% to 113.9%, 82.4% to 112.0%, and 79.8% to 93.4% with corresponding coefficients of variation of 4.1% to 11.7%, 7.5% to 11.5%, and 4.8% to 8.7% for egg, honey, and pork samples, respectively. The developed TRFN–ICA was also systematically compared with high‐performance liquid chromatography coupled with tandem mass spectrometry (HPLC–MS/MS) by analyzing 45 actual samples from egg, honey, and pork. CONCLUSION: Overall, the developed TRFN–ICA had high reliability and excellent potential for the ultrasensitive detection of SMZ for food safety monitoring, also providing a universal platform for the on‐site detection of other targets. © 2020 Society of Chemical Industry